RISK TRANSPARENCY AND CORPORATE GOVERNANCE: KEYS TO ENHANCING FIRM VALUE IN INDONESIA'S BANKING SECTOR - Imanuriea Annisa Putri; Luke Suciyati Amna (CV. Radja Publika, 2026)
This study examines the effect of Corporate Risk Disclosure (CRD) and Good Corporate Governance (GCG) on firm value in banking companies listed on the Indonesia Stock Exchange during 2022-2024. Firm value is measured using Tobin's Q, CRD through a risk disclosure index, and GCG through independent commissioners, audit committees, and institutional ownership. A quantitative explanatory design was applied. Using purposive sampling, 23 banks were selected, yielding 69 firm-year observations. Secondary data were obtained from annual reports and financial statements and analyzed using multiple linear regression. The results show that CRD has a positive and significant effect on firm value. Independent commissioners, audit committees, and institutional ownership also have positive and significant effects on firm value. These findings indicate that broader risk transparency and stronger governance mechanisms can reduce information asymmetry, strengthen investor confidence, and enhance the market value of Indonesian banking companies.